Teledentistry and its application in pediatric dentistry: A literature review - Uchôa, Sue Ann Castro Lavareda; Corrêa, Suelen Castro Lavareda; Corrêa, Davi Lavareda; Corrêa, Vânia Castro; Dias, Hércules Bezerra (Seven Editora, 2024)
During the unfortunate scenario of the COVID-19 pandemic, restrictive measures were implemented in face-to-face dentistry interactions, aiming to promote social distancing and contain the spread of the virus. Given this context, teledentistry has emerged as a solution to offer dental services. The purpose of this article is to review the literature and available information on the provision and use of teledentistry as a method to meet the oral health needs of pediatric patients. Teledentistry has been applied in the pediatric population for oral health education and promotion, remote diagnosis and monitoring, and behavior guidance. This strategy has been shown to be beneficial in enabling dental treatment in remote locations with limited access to pediatric dental specialists. In addition, teledentistry has been shown to be useful in monitoring between appointments, conducting remote diagnosis and screening programs, promoting oral health through dental education, and providing pre-consultation behavioral guidance. This method has proven especially effective during the COVID-19 pandemic, allowing dentists to conduct consultations via their mobile devices and webcams, maintaining a safe distance and avoiding exposure to the virus, both for themselves and patients. Additionally, teledentistry can function as a complement to in-person pediatric dental care methods, resulting in more effective patient management. DOI: https://doi.org/10.56238/sevened2023.007-038